2016
DOI: 10.1289/ehp.1409164
|View full text |Cite
|
Sign up to set email alerts
|

Desert Dust Outbreaks in Southern Europe: Contribution to Daily PM 10 Concentrations and Short-Term Associations with Mortality and Hospital Admissions

Abstract: Background:Evidence on the association between short-term exposure to desert dust and health outcomes is controversial.Objectives:We aimed to estimate the short-term effects of particulate matter ≤ 10 μm (PM10) on mortality and hospital admissions in 13 Southern European cities, distinguishing between PM10 originating from the desert and from other sources.Methods:We identified desert dust advection days in multiple Mediterranean areas for 2001–2010 by combining modeling tools, back-trajectories, and satellite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(108 citation statements)
references
References 45 publications
5
102
0
1
Order By: Relevance
“…An estimated effect of 3% decline in daily forced expiratory volume (FEV1) change was observed for every 10 µg/m 3 increase in ambient PM 10 level [48]. Other studies showed a strong association between dust events and asthma admissions in Japan [23], Trinidad [22], Taiwan [49], South Korea [50,51] and southern Europe [52].…”
Section: Discussionmentioning
confidence: 94%
“…An estimated effect of 3% decline in daily forced expiratory volume (FEV1) change was observed for every 10 µg/m 3 increase in ambient PM 10 level [48]. Other studies showed a strong association between dust events and asthma admissions in Japan [23], Trinidad [22], Taiwan [49], South Korea [50,51] and southern Europe [52].…”
Section: Discussionmentioning
confidence: 94%
“…The DustTrak instrument provides measurements of mass concentration from 0.001 to 150 mg¨m´3 with the mass fraction concentrations corresponding to PM 1 , PM 2.5 , PM 4 , PM 10 , and the total PM 15 . Five minute measurements were made at each stop in the dust plume, consisting of 60 five-second sampling periods.…”
Section: Instrumentation and Measurement Setupmentioning
confidence: 99%
“…Table 1 shows the mean PM [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] concentrations at different locations (Figure 1) inside the dust plume. Although the PM 10 concentrations are moderate (<600 µg¨m´3) for an ongoing dust storm in Iceland, the mean levels of PM 1 are considerably high, such as >97 µg¨m´3 for Storm 1.…”
Section: Size Partitioning Of the Pm Components Of Icelandic Dustmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling the transport of desert dust is receiving increasing attention from the scientific community, allowing for better ascertaining its impact on radiation budget (Hsu et al, 1999), clouds (Bangert et al, 2011), air quality (Goudie andMiddleton, 2001;Pey et al, 2013;Barnaba et al, 2017) and human health (e.g., Mallone et al, 2011;Stafoggia et al, 2016). Despite many improvements in characterizing dust source regions thanks to satellite products Schepanski et al, 2012), modeling dust emission and transport is still challenging due to the high uncertainties associated with the diffuse character of the emissions, re-suspension processes, the inherent complexity of aerosol chemistry, and meteorological conditions, which strongly influence dust outbreaks and their spatiotemporal fields (e.g., Knippertz and Todd, 2012).…”
mentioning
confidence: 99%